2020
DOI: 10.1007/s13365-020-00841-4
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan degradation is associated with risk-taking propensity in methamphetamine users with treated HIV infection

Abstract: Few studies have examined neuroimmune pathways that could contribute to impulsivity in people living with HIV who use substances. Eighty-four methamphetamine-using, sexual minority men with an undetectable HIV viral load were administered the Balloon Analogue Risk Task (BART), a behavioral measure of risk-taking propensity. We examined the associations between kynurenine/tryptophan ratio and phenylalanine/tyrosine ratio with BART scores using multiple linear regression. A higher kynurenine/tryptophan ratio was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Risk-taking profiles may show high concordance with neurocognitive dysfunction in depressed PWH given that HIV-associated neuroinflammation preferentially targets these frontostriatal circuits that support higher-order neurocognitive functions, emotional regulation, and reward processing (Soontornniyomkij et al 2016 ; Woods et al 2009 ). A recent study in stimulant-using PWH identified an association between higher BART scores and greater tryptophan degradation (Lee et al 2020 ), a marker of immune activation and serotonin deficiency that is implicated in HIV-related depression (Gostner et al 2015 ). At the neurocircuit level, HIV disease has been associated with reduced resting-state frontostriatal connectivity, which in turn correlated with higher odds of NCI (Ipser et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Risk-taking profiles may show high concordance with neurocognitive dysfunction in depressed PWH given that HIV-associated neuroinflammation preferentially targets these frontostriatal circuits that support higher-order neurocognitive functions, emotional regulation, and reward processing (Soontornniyomkij et al 2016 ; Woods et al 2009 ). A recent study in stimulant-using PWH identified an association between higher BART scores and greater tryptophan degradation (Lee et al 2020 ), a marker of immune activation and serotonin deficiency that is implicated in HIV-related depression (Gostner et al 2015 ). At the neurocircuit level, HIV disease has been associated with reduced resting-state frontostriatal connectivity, which in turn correlated with higher odds of NCI (Ipser et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated neopterin is consistently correlated with conversion of tryptophan to kynurenine, resulting in less serotonin synthesis. Plasma and CSF levels of serotonin are reduced in PWH [44][45][46] and greater tryptophan degradation (indexed by kynurenine/tryptophan ratios) has been linked to depression 20,47 and impulsivity/risk-taking 48 in PWH. In addition to serotonergic deficiencies, neopterin also correlates with decelerated conversion of phenylalanine to tyrosine, resulting in less dopamine synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanistic importance of tryptophan catabolism is supported by in vitro experimental findings that 3-hydroxyanthranilic acid (a catabolite of tryptophan) decreases the ratio of Th 17 to regulatory T cells in peripheral blood mononuclear cells ( 84 ). Because tryptophan catabolites cross the blood-brain barrier ( 96 ), there is also biological plausibility for observed associations of tryptophan depletion in plasma with cognitive impairment, depressed mood, anhedonia, and impulsivity in PWH ( 85 , 97 , 98 ).…”
Section: This Is Now: Microbiome-gut-brain Axis Alterations Relevant ...mentioning
confidence: 99%